The Jesuits and the Spanish College of Bologna: The Constitutional Oath of 1820 - Nieto Sánchez, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
Many of the Jesuits who left the Peninsula after the Pragmatic of Charles III set his exile on Italian soil. The city of Bologna, in possession of the popes, was the place chosen for many of them and there they found a Spanish institution founded by Cardinal Gil de Albornoz centuries ago, the College of San Clemente of the Spaniards. For years the jesuitical world’s relationship with the Spanish College was intense and fluent, but this situation changed due to the regalistic orders from the Court of Spain which depended directly. This article seeks to highlight this relationship and an event of singular importance, until now unknown, the few parents expelled who remained in the city in 1820 swore the Cadiz Constitution at the College , the royalist clergy Simón Rodríguez Laso, who took the oath. This is the last relationship known between the Jesuits and College of San Clemente of the Spaniards, which until now no new was known.
Keywords: jesuits; College of San Clemente; Bologna; 1812 Constitution; Liberal Triennium